Charity Begins at Home: Understanding the Role of Corporate Social Responsibility and Human Resource Practices on Employees’ Attitudes During COVID-19 in the Hospitality Sector - John, Albert; Shahzadi, Gulnaz; Khan, Kanwal Iqbal; Chaudhry, Shafaq; Sarwar Bhatti, Muhammad Arslan (Frontiers in Psychology, 2022)
The COVID-19 outbreak wreaked havoc on the hospitality business, resulting in significant layoffs, salary cuts, and unpaid leaves globally. This study uses the sensemaking theory to investigate how COVID-19 induced unfavorable human resource (HR) practices affect the link between perceived corporate social responsibility (CSR) and employee identification and commitment. We tested this model using the data collected from 392 hospitality sector employees in Pakistan. The results reveal that “cut in salaries” and “work from home” positively moderate CSR’s impact on employees’ identification and commitment. On the other hand, employee layoff and leave without pay do not impact the positive relationship between CSR and employees’ attitudes. Furthermore, the study finds that CSR during this pandemic has a significant positive impact on employees’ attitudes. However, this relationship becomes insignificant for employees who reported unfavorable HR practices in their organizations. The finding further reveals that CSR’s impact during COVID-19 on employees’ attitudes is moderated by the different levels of CSR importance in employees’ minds. This evidence is significant since HR practices implemented during this crisis need to be identified and framed to understand the effects of CSR on employee commitment and identification. CSR involvement in the pandemic can help managers keep their employees committed to organizations; only if this charity begins from their internal stakeholders first.